Aerospace health: a systematic review and current state of science - Dino, Michael Joseph; Villafuerte, Chloe Margalaux; Pimentel, Justin; Sayat, Jerald; Vital, Joseph Carlo; Hernandez, Danny; Thiamwong, Ladda; Decker, Veronica; Shattell, Mona; Cruz, Luis Ezra; Leoncio, Mary; Reyes, Joshua Rejs; et al. (Frontiers in Space Technologies, 2026)
IntroductionThe frontier of aerospace health integrates medicine, technology, psychology, and related disciplines. The field has evolved from its earlier emphasis on maintaining crew survival beyond Earth’s atmosphere to addressing the fundamental challenge of sustainable human space habitation. Despite the growing body of literature in aerospace health, a gap persists due to an overconcentration on synthesis studies with limited empirical validation and insufficient attention to higher-order human health needs, including psychosocial aspects. By examining existing literature, this systematic review aims to present the current landscape of aerospace health research and its future directions.MethodsThe research paper adopted an integrative review framework developed by Whittemore et al. (Journal of Advanced Nursing, 2005, 52(5), 546–553), comprising five stages: problem identification, literature search, data evaluation, data analysis, and data presentation.Results and DiscussionThe Results and Discussion are organized into three sections that reflect the study’s objectives: (1) to focus on bibliometric patterns of the field, (2) to demonstrate study purposes and health-related outcomes, and (3) to conduct keyword network analysis and thematic linkages among the included articles. Findings indicate that most studies reviewed in aerospace health involve multiple authors, show a notable increase after the COVID‐19 pandemic, and are primarily concentrated in the Americas. The results can be attributed to the multidisciplinary nature of the aerospace industry, the post-pandemic expansion of space activities, and the dominance of U.S.-led space initiatives. In addition, article purpose and outcomes demonstrate eight themes identified across all articles, covered under: (1) Physiology and Health Risks, (2) Psychology and Behavior, (3) Pharmaceuticals and Interventions, (4) Product and Technology, (5) Profession and Training, (6) Process and Procedures, (7) Place and Environment, and (8) Policy and Strategy. Keywords and network analysis, on the other hand, determine six themes, namely: (1) Health Ecosystem, (2) Health Examination, (3) Health Education, (4) Health Engineering, (5) Health Estimation, and (6) Health Evidence.ConclusionUltimately, the review presents a Torus Model and thematic analyses that map the current landscape of aerospace health research and provide insights for future directions of the field.Systematic Review Registrationhttps://www.osf.io/97u8f